Diagnosis and Management of Cerebral Small Vessel Disease. Issue 2 (April 2023) - Sharrief, Anjail
ABSTRACT: OBJECTIVE: Cerebral small vessel disease (CSVD) is a common neurologic condition that contributes to considerable mortality and disability because of its impact on ischemic and hemorrhagic stroke risk and dementia. While attributes of the disease have been recognized for over two centuries, gaps in knowledge remain related to its prevention and management. The purpose of this review is to provide an overview of the current state of knowledge for CSVD. LATEST DEVELOPMENTS: CSVD can be recognized by well-defined radiographic criteria, but the pathogenic mechanism behind the disease is unclear. Hypertension control remains the best-known strategy for stroke prevention in patients with CSVD, and recent guidelines provide a long-term blood pressure target of less than 130/80 mm Hg for patients with ischemic and hemorrhagic stroke, including those with stroke related to CSVD. Cerebral amyloid angiopathy is the second leading cause of intracerebral hemorrhage and may be increasingly recognized because of newer, more sensitive imaging modalities. Transient focal neurologic episodes is a relatively new term used to describe "amyloid spells." Guidance on distinguishing these events from seizures and transient ischemic attacks has been published. ESSENTIAL POINTS: CSVD is prevalent and will likely be encountered by all neurologists in clinical practice. It is important for neurologists to be able to recognize CSVD, both radiographically and clinically, and to counsel patients on the prevention of disease progression. Blood pressure control is especially relevant, and strategies are needed to improve blood pressure control for primary and secondary stroke prevention in patients with CSVD.